Desenvolvimento experimental e simulação numérica de uma réplica térmica de placa de circuito impresso - Cunha, Alex Pereira da [UNESP] (2014)
This paper proposes a modeling of a thermal replica of the printed circuit board, made from components with known power aimed at analyzing the temperature distribution and the processes of heat exchange when similar elements are used together in the electronic systems, as that with the increasing need for higher processing components are smaller and more heat dissipating. The heated obstacles simulating components are in a trade resistor surrounded by special resin for electronic encapsulation. This model will be created to be their governing equations solved in commercial software. The thermal replica is represented by blocks with different power dissipation and heat exchange areas. Once the overall thermal performance depends on the thermal dissipation of each block, the evaluation can tell which blocks contribute to better efficiency in heat exchange. The experiments provide the values of the temperature and velocity components of flow to be compared with the computational model, and thus the turbulence model that best describes the experimental analysis can be found. The application of the theory of influence coefficients between components was also studied. This work is suitable for the identification of problems that relate directly or indirectly to failures in electronic components due to high temperature